Program PSN (Pemberantasan Sarang Nyamuk) Sebagai Upaya Pencegahan Demam Berdarah Dengue (DBD) - Khanifah, Farach; Susanto, Awaluddin; Arifin, M. Zainul; Ramandha, Bima (Yayasan Daarul Huda Kruengmane, 2026)
Dengue Hemorrhagic Fever (DHF) is a communicable disease caused by the dengue virus and transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. The high incidence of DHF in Indonesia highlights the need for continuous prevention and control efforts, one of which is the 3M Plus Mosquito Nest Eradication Program (PSN) that actively involves community participation. This community service activity aims to support DHF prevention and control through mosquito larva inspections in the household environment of residents in Mayangan Village, Jombang Regency. The method used was door-to-door inspection of mosquito larvae in household bathroom water containers, involving the Mayangan Health Center (Puskesmas), health cadres, and students from the D3 Medical Laboratory Technology Study Program. The target of the activity was household bathrooms in Mayangan Village. The results showed that out of 33 bathrooms inspected, 7 bathrooms (21.2%) were positive for mosquito larvae, while 26 bathrooms (78.8%) had no larvae. For the houses where larvae were found, larvicide (Abate) was applied as a control measure. The PSN activities were carried out smoothly and received positive responses from the community. It can be concluded that the PSN program plays an important role in raising public awareness and reducing the risk of DHF transmission through sustainable vector control.